From Mandate to Acceptance: The Role of Principals and Policy Communication in Islamic School Digitalization - Andik Riyanto; Saputranur Saputranur; Miftahul Huda (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze policy communication and acceptance in the implementation of school digitalization in Islamic educational institutions (madrasas). This study used a qualitative case study design. Data collection was conducted through in-depth interviews, participant observation, and documentation studies. The results indicate that the acceptance of digitalization policies is significantly influenced by how policy messages are communicated, understood, and interpreted by implementers at the school level. Policy communication is more effective when principals provide clear directions, practical explanations, and ongoing support throughout the implementation process. However, policy acceptance still faces several obstacles, such as limited training, unstable digital infrastructure, and disparities in digital competency among policy implementers. Furthermore, this study found that educational actors in madrasas assess digitalization not only from a technical and efficiency perspective, but also from the perspective of its alignment with Islamic values and school culture. These considerations influence policy acceptance and implementation in the field. The implementation of digitalization in madrasas requires dialogic policy communication, institutional readiness, and leadership capable of bridging policy with contextual educational practices. These findings contribute to the development of digitalization policies in Islamic educational units that are more adaptive and sensitive to local values.